Peningkatan Minat Wisatawan Domestik Terhadap Destinasi Wisata Di Kabupaten Boalemo - Fibriyanti S. Lakoro (Yayasan Literasi Sains Indonesia, 2022)
Tourism has an important role in building the Indonesian economy, where the improvement of the country's economy will be able to introduce a sense of love for the homeland and introduce the arts, culture, nation and natural beauty of Indonesia. The purpose of the study was to determine and describe the increasing interest of domestic tourists towards tourist destinations in Boalemo Regency. The research method used in this research is descriptive qualitative. Data collection methods used are observation, interviews and documentation. So the data analysis technique used is Miles and Hubberman conducted by interviews, documentation and other research instruments. The results of the research and discussion are 1) Services are very important which must be improved by the Tourism Office and tourism managers. By fulfilling expectations that can increase and give more attention to existing visitors. 2) Facilities are very important considering that they greatly affect tourist visits to existing tourist destinations. Such as the needs of sellers or other supporting facilities. 3) The environment is very important to pay attention to because the environment greatly influences the interest of local tourists to visit local tourist destinations in Boalemo Regency. 4) Security and comfort affect the interest of tourist visits because they will affect the conditions and comfort of tourism at tourist sites